LINGUISTIC MEANS OF EXPRESSING THE HOMELAND CONCEPT IN ENGLISH AND UZBEK PAREMIOLOGY - Komilova Sabrina Sanjarovna,Mardiyev Tulkin Kulibayevich (Ethiopian International Journal of Multidisciplinary Research, 2026)
This article explores the linguocultural and semantic peculiarities of the concept “Homeland” as reflected in the paremiological systems of the English and Uzbek languages. Proverbs and sayings, being the quintessence of folk wisdom, serve as a primary source for revealing a nation’s worldview, national values, and emotional attachment to its territory. The research utilizes comparative-typological and semantic analysis to identify the specific linguistic means - such as metaphors, personification, epithets, and symbolic imagery - used to conceptualize the notion of “motherland” or “home.” The findings indicate that while English paremiology frequently emphasizes the comfort, safety, and privacy of the domestic “home”, Uzbek proverbs elevate the concept of “Vatan” to a sacred status, often associating it with maternal bonds, ancestral soil, and the inherent value of one's birthplace (Vatan ostonadan boshlanadi). This comparative study contributes to the fields of cognitive linguistics and linguoculturology, offering insights into the diverse ways in which linguistic structures encode national identity and patriotic sentiment across different cultures.